Factor using the gcf : 6x^3-9x^2+12x

9x^2-12x=0Simple and best practice solution for 9x^2-12x=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework. If it’s not what You are looking for type in the equation solver your own equation and let us solve it. Equation: Solution for 9x^2-12x=0 equation:
Simplifying 9x2 + -12x = 0 Reorder the terms: -12x + 9x2 = 0 Solving -12x + 9x2 = 0 Solving for variable ’x’. Factor out the Greatest Common Factor (GCF), ַx’. 3x(-4 + 3x) = 0 Ignore the factor 3. Subproblem 1Set the factor ’x’ equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0 Subproblem 2Set the factor ’(-4 + 3x)’ equal to zero and attempt to solve: Simplifying -4 + 3x = 0 Solving -4 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add ָ’ to each side of the equation. 4 + 4 + 3x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 3x = 0 + 4 3x = 0 + 4 Combine like terms: 0 + 4 = 4 3x = 4 Divide each side by ַ’. x = 1.333333333 Simplifying x = 1.333333333Solutionx = {0, 1.333333333}

6x^3-9x^2+12x
Their GCF is 3x so
3x(2x^2-3x+12)


RELATED: